Volatile profiles of commercial vetch prepared via different processing methods. (30th November 2022) - Riley, Samuel; Lale, Aneesh; Nguyen, Vy; Xi, Hangwei; Wilkinson, Kerry; Searle, Iain R.; Fisk, Ian
Highlights: The volatile profiles of vetch species were established for the first time. Intraspecies variation was observed between commercial and wild varieties. Novel processing methods, including natto and tempeh fermentation, were evaluated. Processing enhanced the flavor profiles of different vetch products. Abstract: Vicia sativa (Common Vetch) is currently an underutilised leguminous crop species with high protein content and superior drought tolerance. This study aimed to understand the mechanisms behind vetch flavor development following processing to facilitate its uptake as a future source of dietary protein. A total of 95 volatile compounds were identified by solid-phase microextraction gas chromatography-mass spectrometry (SPME GC–MS) for a range of vetches processed by dehulling, soaking, germination, microwaving, and fermentation. 2-pentyl furan, benzyl alcohol, benzaldehyde, 1-octen-3-ol and 1-hexanol were found to be characteristic aroma compounds of V. sativa. Analysis of a V. sativa landrace demonstrated significant intraspecies variation in volatile abundance, three-fold that of commercial varieties. Both natto and tempeh fermentation produced significant quantities of alcohols, esters, and carboxylic acids with specifically natto generating significant pyrazines. Concentrations of 1-octen-3-ol significantly decreased after tempeh fermentation indicating its potential to reduce documented off flavor generating volatiles within V. sativa .